(untitled) (Research, Society and Development, 2022)
Indonesia is an archipelagic country in which abundant biological resources and ecosystems, including wild animals, are protected by laws and regulations. Legal protection for protected wild animals is regulated in law number 5 of 1990 concerning the conservation of living natural resources and their ecosystems, that acts prohibited by this law if violated will be subject to sanctions. In implementing legal protection for protected wild animals, it is the responsibility of the Natural Resources Conservation Agency and other law enforcers. In the implementation of legal protection for protected wild animals there are still many cases that occur and are not resolved, in this legal protection the role in law enforcement should be maximized. The urgency of this research is about legal protection carried out by related parties that have not been handled properly. This research is an empirical normative legal research which is conducting legal research that knows legal protection in accordance with the law and what is happening in the field. This research shows that there are inhibiting factors in the protection of wild animals protected by law enforcement, this can be detrimental to the community in the future if there are still problems that should be solved by increasing coordination between law enforcers.